Circular RNA circFOXO3 facilitate non-small cell lung cancer progression through upregulating HMGB3 via sponging miR-545-3p/miR-506-3p. (April 2022) - Yang, Minglei; Zheng, Enkuo; Ni, Junjun; Xu, Xiang; Jiang, Xu; Zhao, Guofang
Highlights: Overexpression of circFOXO3 promotes the development NSCLC. Circ-FOXO3 could sponge miR-545-3p and miR-506-3p to upregulated HMGB3. Upregulation of HMGB3 facilitates NSCLC progression. circRNA-miR-545-3p/miR-506-3p-HMGB3 network could be a therapeutic target of NSCLC. Abstract: Purpose: Circular RNAs (circRNAs) have emerged as a pivotal regulatory element in the progression of human cancers. Being an important member of circRNAs, circFOXO3 has been implicated in tumor invasion or metastasis of non-small cell lung cancer (NSCLC); however, the molecular mechanism underlying this promoting effect remains an enigma. The present study aims to study the function of circFOXO3 and dissect the relevant intracellular network in the progression and metastasis of NSCLC. Methods: Quantitative real time PCR (RT-qPCR) assay and Western blotting were used to quantify the levels of RNAs and proteins respectively. starBase v2.0 and luciferase assay were used to validate the target of circRNAs or miRNAs. Cell Counting Kit-8 (CCK-8) assay was adopted to examine cell viability. Transwell was used to determine cell invasion and migration. Xenograft model was established to detect tumor growth. Results: RT-qPCR showed that circFOXO3 was overexpressed in NSCLC cells and tissues. Knockdown of circFOXO3 not only inhibited NSCLC cell proliferation, migration and invasion in vitro but also suppressed tumor growth in vivo . starBase v2.0 and luciferase assay results collectively suggested that circFOXO3 sponged miR-545-3p and miR-506-3p. Dual-inhibition of circFOXO3 and its target miRNAs suppressed the reduction of cell proliferation, migration and invasion induced by siRNA of circFOXO3 (si-circFOXO3), demonstrating that the effect of circFOXO3 on NSCLC was dependent on sponging miR-545-3p and miR-506-3p. Further bioinformatic analysis and biochemistry experiments revealed that miR-545-3p and miR-506-3p regulated the expression of a family member of high-mobility group box, HMGB3. Conclusion: Here, we show thatcircFOXO3 in NSCLC promotes the proliferation, migration and invasion of NSCLC cells, thereby promoting tumor growth. We further find that circFOXO3 sponges miR-545-3p/miR-506-3p that bind to 3′-UTR of HMGB3 mRNA, which constitutes the major network fulfilling the circFOXO3′s promoting effect. Therefore, we proposed that circFOXO3 could be a potential therapeutic target for NSCLC.